Enhancing the transparency of accounting research: the case of narrative analysis. Issue 1 (20th April 2015) - De Loo, Ivo; Cooper, Stuart; Manochin, Melina
Abstract : Purpose: – This paper aims to clarify what 'narrative analysis' may entail when it is assumed that interview accounts can be treated as (collections of) narratives. What is considered a narrative and how these may be analyzed is open to debate. After suggesting an approach of how to deal with narrative analysis, the authors critically discuss how far it might offer insights into a particular accounting case. Design/methodology/approach: – After having explained what the authors' view on narrative analysis is, and how this is linked with the extant literature, the authors examine the socialisation processes of two early career accountants that have been articulated in an interview context. Findings: – The approach to narrative analysis set out in this paper could help to clarify how and why certain interpretations from an interview are generated by a researcher. The authors emphasise the importance of discussing a researcher's process of discovery when an interpretive approach to research is adopted. Research limitations/implications: – The application of any method, and what a researcher thinks can be distilled from this, depends on the research outlook he/she has. As the authors adopt an interpretive approach to research in this paper, they acknowledge that the interpretations of narratives, and what they deem to be narratives, will be infused by their own perceptions. Practical implications: – The authors believe that the writing-up of qualitative research from an interpretive stance would benefit from an explicit acceptance of the equivocal nature of interpretation. The way in which they present and discuss the narrative analyses in this paper intends to bring this to the fore. Originality/value: – Whenever someone says he/she engages in narrative analysis, both the "narrative" and "analysis" part of "narrative analysis" need to be explicated. The authors believe that this only happens every so often. This paper puts forward an approach of how more clarity on this might be achieved by combining two frameworks in the extant literature, so that the transparency of the research is enhanced.